Influence of deep excavation induced ground movements on adjacent piles - Nishanthan, R.; Liyanapathirana, D.S. (Elsevier, 2016)
In urban areas, excavations for cut-and-cover tunnels and basement construction cause detrimental effects on adjacent existing piles. Hence quantifying the excavation induced lateral deformations and bending moments on piles are important to ensure the stability of structures. In this paper, behaviour of a single pile subjected to excavation induced ground movements is analysed using the finite element method, which has the ability to simulate the construction sequence comprising soil excavation, defor mations due to dewatering within the excavation and installation of struts. A fully coupled analysis is car ried out based on the effective stress principle. The numerical model was verified using the centrifuge test data found in the literature. A parametric study was carried out to establish the excavation induced pile behaviour varying the depth of the excavation, soil properties, wall support system, pile fixity con ditions and pile location with respect to the excavation. Increasing axial load does not have a significant influence on the pile behaviour. However, pile head fixity condition, and stiffness and spacing of the wall support system have a significant influence on the pile behaviour adjacent to the excavation. Finally, based on the parametric study, a set of design charts are developed to predict the pile behaviour by taking into account the depth of excavation, undrained shear strength, width of the pile, spring stiffness, spacing of vertical supports, and unsupported depth of the excavation. The capability of the proposed design charts are demonstrated using a three-dimensional finite element analysis, a case study from the litera ture and a previously published simplified analysis procedure.
Keywords: Deep excavations; Ground movements; Wall support systems; Finite element method; Pile behaviour